PENGARUH FRAUD HEXAGON DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2017 – 2021) - Ridwan, Izzah Aulia; Nasir, Azwir; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aimed to analyze the influence of the six elements in Hexagon Theoryto detect possible Financial Statement Fraud in consumer goods industry sectorcompanies listed on the Indonesia Stock Exchange (IDX). Fraudulent financialstatements is measured using the F-Score Model. The population of this study isthe consumer goods industry sector companies listed on the Indonesia StockExchange (IDX) 2017-2021. The type of data used are secondary data in the formof financial and annual reports of companies listed on the Stock Exchange. Thisstudy used purposive sampling and obtained 23 companies with 115 observations.The collected data is analized using logistic regression using SPSS (StatisticalProduct and Service Solutions) version 23. This study found that capability byproxy director experience significantly influence the financial statements fraud.As for stimulus by proxy return on assets, collusion by proxy state ownedentreprised, opportunity by proxy innefective monitoring, rationalization by proxychange of auditor, and ego by proxy dualism position do not have significantinfluent on financial statements fraud.Keywords : Fraud Hexagon Theory, F-Score model, Fraudulent FinancialStatement